2014
DOI: 10.2310/8000.2013.131069
|View full text |Cite
|
Sign up to set email alerts
|

Drowning: an overlooked cause of out-of-hospital cardiac arrest in Canada

Abstract: Introduction: Drowning is a major public health concern, yet little is known about the characteristics of drowning patients. The objectives of this study were to describe the demographic and clinical characteristics of out-of-hospital cardiac arrest (OHCA) attributed to drowning in Ontario and to compare the characteristics of OHCA attributed to drowning to those of presumed cardiac etiology. Methods: A retrospective, observational study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…About half of the study population benefited from a BLS provided by a witness before professional first aid provider arrival (41.9% had chest compression and 17.9% had ventilation). The median no flow duration (time interval between cardiac arrest and first cardiopulmonary resuscitation) was 10 minutes. First aid providers (usually firemen or lifeguards) initiated a BLS in 85.0% of cases before MMT arrival (median response time 10 minutes).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…About half of the study population benefited from a BLS provided by a witness before professional first aid provider arrival (41.9% had chest compression and 17.9% had ventilation). The median no flow duration (time interval between cardiac arrest and first cardiopulmonary resuscitation) was 10 minutes. First aid providers (usually firemen or lifeguards) initiated a BLS in 85.0% of cases before MMT arrival (median response time 10 minutes).…”
Section: Resultsmentioning
confidence: 99%
“…Our study also confirms some previous investigations concerning the outcome predictive factors timings (MMT response time or no flow duration) . However, this work outlines the necessity of an organized quick and high quality BLS . Indeed, we shown that an immediate care by witnesses (a short no flow duration) is a sine qua none condition to survive with a good neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusion of drowning publications that did not explicitly mention that data collection was based on the USFD parameters, eight USFD based drowning publications remained [ 3 10 ]. Of the 29 publications that had not used the USFD, three were drowning publications of which data collection was based on the Utstein style for out of hospital cardiac arrest [ 20 , 21 ], or did not describe the use of any Utstein template [ 22 ], four were publications on resuscitation that included only a few drowning patients [ 23 26 ], one was a resuscitation publication that excluded drowning victims [ 27 ], five were reviews [ 28 32 ], and 16 were other types of publications (definition of drowning, editorials, abstracts, letter to the editor, non-English language articles, post mortem examinations, book chapter) [ 33 – 48 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%